Exocrine pancreatic insufficiency and hyperoxaluria: a preventable renal complication from gastroenterology - Hornung, Ernesto (2026)
Exocrine pancreatic insufficiency (EPI) is the inability of the pancreas to produce essential digestive enzymes for fat metabolism, leading to systemic and nutritional repercussions. Although its manifestations are typically digestive, systemic complications such as enteric hyperoxaluria can occur. We present a 68-year-old man with insulin-dependent diabetes mellitus, who developed steatorrheic diarrhea and significant weight loss. Computed tomography revealed an atrophic pancreas with diffuse calcifications. Based on a diagnosis of chronic pancreatitis, pancreatic enzyme replacement therapy (PERT) was initiated empirically with clinical improvement. Three years later, while asymptomatic from a gastrointestinal perspective, he developed bilateral calcium oxalate nephrolithiasis progressing to end-stage renal disease, requiring hemodialysis. This was interpreted as oxalate nephropathy secondary to enteric hyperoxaluria, favored by suboptimal PERT dosing and poor follow-up adherence. PERT was optimized to 40,000 units per meal with good nutritional and digestive outcomes. The etiological study for EPI showed no obstructive or systemic causes. This case highlights the importance of suspecting EPI when systemic complications like secondary hyperoxaluria appear. Early diagnosis remains challenging and requires close monitoring, as specific guidelines to prevent irreversible renal damage are lacking; early recognition can significantly improve prognosis and quality of life.